Distribuição espaço-temporal de uma comunidade de anfíbios anuros no sul da Amazônia - Noronha, Janaina da Costa de (2012)
The biotic and abiotic factors are responsible for the structuring of animal and plant communities in the Amazonia and generate patterns of species distribution. The objectives of this study were to evaluate the effects of environmental variables on the spatial distribution of a community of frogs in the Southern Amazon, check for changes in community composition of frogs during the rainy season and to compare the number of species and number of individuals with standardized studies the frogs in the Brazilian Amazonia. There were three samples of frogs during the rainy season (beginning, middle and end). At each sample was covered 12 plots of 250 m, distributed in area of 5 km² in the São Nicolau Farm, Cotriguaçu, Mato Grosso. We used simultaneous visual encounter surveys and auditory sampling. Environmental variables collected in each plot were: number of trees, altitude, pH, percentage of clay and sand soil, canopy cover, litter volume and distance to nearest stream. The dimensionality of the data was reduced to two dimensions by the method of non-metric multidimensional scaling (NMDS) using data on abundance and occurrence. To analyze the influence of environmental variables on the spatial distribution pattern of the community we used multivariate multiple regressions. The temporal variation of the community of species was analyzed with data occurring through the analysis of Procrustes. It is reported the presence of 466 individuals in 21 species. The species that presented the greatest number of individuals was Pristimantis sp (67.9% of total). The altitude affected the composition of anuran species with abundance data. There was difference in community composition between the frogs beginning, middle and end of the rainy season. The result of this study shows that the community composition of amphibians is structured by the altitude, indicating the importance of the availability of reproductive habitats for species distribution. The study area of 5 km² is home to a proportionally greater number of species than other localities of the Amazonia, but with a smaller number of individuals, highlighting the importance of further studies in unexplored regions for greater understanding of the biodiversity of the region and its structuring factors.